Keahlian Auditor, Pengetahuan Auditor, dan Kompleksitas Tugas terhadap Audit Judgment pada Kantor Akuntan Publik di Semarang - Hermawan Triono (Jurnal Ilmiah Aset, 2021)
This study aims to determine the effect of Auditor Expertise, Auditor Knowledge and Task Complexity on Audit Judgment at a Public Accounting Firm in Semarang. The population contained in this study is the Auditor who served at the Public Accounting Firm in Semarang with the number of respondents as many as 34 auditors. The method of determining the sample using the census technique. Data analysis used multiple linear analysis. The results of the analysis show that Auditor expertise and Auditor knowledge have a positive effect on Audit judgment, while task complexity has no effect on Audit judgment.